PENERAPAN PEMBELAJARAN BERBASIS POWER POINT UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SANTRI DI LINGKUNGAN PONDOK PESANTREN - Leo Kurniawan; Khoiril Akhbar (Universitas Islam Negeri Mataram, 2026)
This study aims to answer the following questions: (1) How is the implementation of the Power Point-based conversation learning method for students in Islamic boarding schools? (2) What are the supporting and inhibiting factors in its implementation? (3) How effective is this method in improving students' conversational skills? In addition, this study aims to identify implementation challenges in the field and compile recommendations for developing a more interesting and efficient Arabic language learning method strategy. Using a qualitative case study method, data were collected through observation, documentation, and purposive sampling interviews. The findings show the effectiveness of Power Point in increasing students' courage, fluency, and motivation, supported by visualization of relevant vocabulary and dialogue, as well as the Islamic boarding school's innovation policy and students' enthusiasm. The main obstacles include busy schedules, limited infrastructure, and variations in teachers' technological competencies. Overall, this integration transforms traditional learning into a more interactive one in the Islamic boarding school environment.